Rare earth doped molybdenum boride composite material, preparation method thereof and application of rare earth doped molybdenum boride composite material in electro-catalytic decomposition of water
The preparation of rare earth-doped MoBx nanoparticles through solid phase method and heat treatment has solved the problem that the harsh synthesis conditions of molybdenum boronide materials and the difficulty in improving catalyst performance in rare earth doping in the prior art, and achieved efficient and long-lasting electrocatalytic decomposition of water hydrogen analysis performance.
Patent Information
- Application Number
- CN202510125425.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the synthesis conditions of molybdenum boride materials are harsh, and it is difficult to obtain a catalyst with superior performance due to the difference in radius when the rare earth elements are doped into MoBx.
A simple solid-phase method combined with heat treatment was used to prepare rare earth element-doped MoBx nanoparticles. By adjusting the reaction conditions of rare earth element lanthanum and molybdenum and boron, a composite material with better electrocatalytic decomposition properties were formed.
The overpotential of the prepared La-MoBx electrode in acidic medium was reduced to 182mV (10 mA cm-2), and it has efficient and long-lasting electrocatalytic decomposition of water hydrogen analysis.
Smart Images

Figure CN119571386A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalysis technology, and in particular to a rare earth doped molybdenum boride composite material, a preparation method thereof, and application thereof in electrocatalytic water decomposition. Background Art
[0002] Molybdenum boride (MoBx) materials have attracted increasing attention in the fields of electrocatalytic water splitting due to their stable physicochemical properties and good electrical conductivity. However, due to the harsh synthesis conditions, the synthesis of pure MoBx materials that can be used for catalytic applications has always been a challenge. Doping with heterogeneous elements has become an effective method to regulate the local electronic structure of Mo-based materials.
[0003] In the prior art, Peng Guiming et al. reported that the surface electronic structure of self-supporting molybdenum boride materials can be regulated by combining with Co, 10mA / cm 2 The lower overpotential can be reduced to 148 mV, and the catalyst's hydrogen evolution activity in water electrolysis is greatly improved. However, the material synthesis method is relatively harsh and has high requirements for the physical phase of molybdenum boride.
[0004] Rare earth element doping can theoretically adjust the electronic environment around the atoms of the main material, thereby improving the catalytic activity. However, due to the huge difference in atomic radius between rare earth elements and other transition metals, it is still a challenge to dope rare earth metal atoms into MoBx to obtain catalysts with better performance. Summary of the invention
[0005] In view of the technical problems existing in the prior art, the purpose of the present invention is to provide a rare earth doped molybdenum boride composite material and its preparation method and application in electrocatalytic water decomposition. Rare earth element doped MoBx nanoparticles are prepared by a simple solid phase method combined with heat treatment. The composite material has better electrocatalytic water decomposition performance than MoBx.
[0006] The technical solution of the present invention is as follows: A rare earth doped molybdenum boride composite material (RE-MoBx), wherein the rare earth element is La, and the molar ratio of the rare earth element to molybdenum is 0.03-0.1:0.97-0.9.
[0007] The method for preparing the rare earth-doped molybdenum boride composite material comprises the following steps: First, the molybdate precursor is mixed with a boron source and a flux in a certain ratio. These raw materials need to be mixed evenly to ensure the consistency and efficiency of the subsequent reaction.
[0008] Addition and grinding of lanthanum salt: Next, add lanthanum salt to the above mixture. Use a grinder to grind the mixture thoroughly to ensure that all components are evenly distributed at the microscopic level. The purpose of grinding is to increase the contact area between the raw materials and promote the reaction.
[0009] Heat treatment: The ground mixture is placed in a high-temperature furnace and heat treated under the protection of an inert atmosphere (such as argon or nitrogen). First, the temperature is raised to the first temperature, i.e. 400-600°C, and maintained for 20-40 minutes. The main purpose of this stage is to promote the initial reaction of the raw materials, including the melting of the flux, the interaction between the raw materials, and the release of gas.
[0010] Further heating and holding: After the first temperature stage is completed, the temperature is further raised to the second temperature, i.e. 700-900°C, and maintained for 3-5 hours. This higher temperature stage is a key step, which ensures the full reaction of the rare earth element lanthanum with molybdenum and boron, forms the desired rare earth doped molybdenum boride structure, and optimizes the performance of the composite material.
[0011] Cooling and post-treatment: After the heat treatment is completed, the product is cooled naturally to room temperature. Subsequently, the product is placed in a water bath at 80-100°C for 1-1.5 hours. This step is intended to dissolve and remove unnecessary fluxes (such as sodium chloride and potassium chloride) and possible boron oxide impurities, thereby improving the purity of the final product.
[0012] Drying: Finally, the product after the water bath treatment is dried to remove moisture and other volatile substances to obtain a dry rare earth-doped molybdenum boride composite material.
[0013] Preferably, the molybdate precursor is ammonium molybdate tetrahydrate, and molybdic acid (H 2 MoO 4 ), lead molybdate (PbMoO 4 )、Lithium molybdate(Li 2 MoO 4 ), potassium molybdate (K 2 MoO 4 )、Ammonium heptamolybdate((NH 4 ) 6 Mo 7 O 24 ) can be replaced by any one or more of the following.
[0014] Preferably, the boron source is boron powder, which can be obtained by using boric acid (H 3 BO 3 ), and sodium borohydride (NaBH) which can be decomposed into boron and amorphous boron at high temperature. 4 )、boron nitride (BN), boric anhydride (B 2 O 3 )replace.
[0015] Preferably, the flux is sodium chloride, potassium chloride, lithium chloride (LiCl), calcium chloride (CaCl 2 ), sodium fluoride (NaF) or sodium carbonate (Na 2 CO 3 ) Any one or more of .
[0016] The rare earth nitrate is lanthanum nitrate, which can be lanthanum oxide (La 2 O 3 )、Lanthanum chloride(LaCl 3 ), lanthanum acetate and citrate.
[0017] Wherein, the first temperature is 400°C.
[0018] Wherein, the second temperature is 800°C.
[0019] The above rare earth doped molybdenum boride composite material is used as a catalyst in electrocatalytic water decomposition.
[0020] Rare earth (RE) elements have attracted increasing attention in electrochemical applications due to their partially filled 4f orbitals and lower electronegativity. When RE elements are doped into host materials, the RE metal atoms donate electrons and change the electronic environment around the host material atoms due to the electronegativity difference between the RE metal and the host material elements. Doping with rare earth elements can effectively adjust the electronic structure of the catalyst, promote the dissociation of water and form active hydrogen adsorbates.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a rare earth element doped MoBx composite material for the first time. The preparation method is simple and can be obtained by a simple solid phase method and heat treatment. The prepared La-MoB x The overpotential of the electrode in acidic medium is 182 mV (10 mA cm -2 ), with efficient and long-lasting electrocatalytic water decomposition and hydrogen evolution performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The structural characterization of MoBx and 5% La-MoBx catalysts prepared in the examples and comparative examples of the present invention; Among them, a, SEM of MoBx; b, SEM of 5% La-MoBx; c, high-resolution electron microscope image of MoBx; d, high-resolution electron microscope image of 5% La-MoBx; ei, EDS spectrum of 5% La-MoBx; Figure 2 Characterization of the electronic properties of MoBx and 5% La-MoBx catalysts prepared in the examples and comparative examples of the present invention; a, X-ray diffraction patterns of MoBx and 5% La-MoBx catalysts, b, high-resolution XPS spectra of B 1s of MoBx and 5% La-MoBx; c, high-resolution XPS spectra of Mo 3d of MoBx and 5% La-MoBx; d, high-resolution XPS spectra of La 3d of MoBx and 5% La-MoBx; Figure 3 The 0.5 MH 2 SO 4 Electrocatalytic HER performance in Among them, a, different samples at 5 mV s -1 IR compensation polarization curve of HER at scanning rate; b, 10 mA cm -2 The overpotential at 1000 nm and the catalyst loading was 0.4 mg cm -2 , the solution internal resistance is 3.2Ω; c, Tafel slope; d, capacitive current at 0.375 V; e, Nyquist plots of different catalysts; f, 5% La-MoB x At 10 mA cm -2 and 50mA cm -2 24h IT curve; g, 5% La-MoB at different current densities x stability; Figure 4 For electrocatalysts at 0.5 MH 2 SO 4 Electrocatalytic full cell performance in Among them, a, polarization curve; b, stability. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0025] Unless otherwise specified, the raw materials, equipment, etc. involved in the present invention are common commercially available products.
[0026] Example 1: A method for preparing a rare earth-doped molybdenum boride composite material, comprising the following steps: First, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, boron powder, NaCl and KCl are precursor, boron source and molten salt respectively. 1.5g NaCl and 1.5g KCl are mixed and ground evenly. 0.1g (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 0.2g boron powder were mixed and ground evenly, the two mixed powders were further mixed and ground together, and lanthanum nitrate was added to continue grinding evenly, wherein the molar ratio of La to Mo was 0.05:0.95. The mixed solid powder was transferred to a porcelain boat, heated to 500℃ at 2℃ / min in an Ar atmosphere, maintained for 30min, and then heated to 800℃ at 5℃ / min, maintained for 4h. After the product was cooled, the obtained material was placed in a water bath at 90℃ for 1h to remove the residual molten salt and B x O y impurities, and then dried in a vacuum oven, recorded as 5% La-MoB x .
[0027] Example 2: A method for preparing a rare earth-doped molybdenum boride composite material, the steps are as follows: First, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, boron powder, NaCl and KCl are precursor, boron source and molten salt respectively. 1.5g NaCl and 1.5g KCl are mixed and ground evenly. 0.1g (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 0.2g boron powder were mixed and ground evenly, the two mixed powders were further mixed and ground together, and lanthanum nitrate was added to continue grinding evenly, wherein the molar ratio of La to Mo was 0.03:0.97. The mixed solid powder was transferred to a porcelain boat, heated to 500℃ at 2℃ / min in an Ar atmosphere, maintained for 30min, and then heated to 800℃ at 5℃ / min, maintained for 4h. After the product was cooled, the obtained material was placed in a water bath at 90℃ for 1h to remove the residual molten salt and Bx O y impurities, and then dried in a vacuum oven, recorded as 3% La-MoB x .
[0028] Example 3: A method for preparing a rare earth-doped molybdenum boride composite material, comprising the following steps: First, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, boron powder, NaCl and KCl are precursor, boron source and molten salt respectively. 1.5g NaCl and 1.5g KCl are mixed and ground evenly. 0.1g (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, 0.2g boron powder were mixed and ground evenly, the two mixed powders were further mixed and ground together, and lanthanum nitrate was added to continue grinding evenly, wherein the molar ratio of La to Mo was 0.07:0.93. The mixed solid powder was transferred to a porcelain boat, heated to 500℃ at 2℃ / min in an Ar atmosphere, maintained for 30min, and then heated to 800℃ at 5℃ / min, maintained for 4h. After the product was cooled, the obtained material was placed in a water bath at 90℃ for 1h to remove the residual molten salt and B x O y impurities, and then dried in a vacuum oven, recorded as 7% La-MoB x .
[0029] Example 4: A method for preparing a rare earth-doped molybdenum boride composite material, comprising the following steps: First, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, boron powder, NaCl and KCl are precursor, boron source and molten salt respectively. 1.5g NaCl and 1.5g KCl are mixed and ground evenly. 0.1g (NH 4 ) 6 Mo 7 O 24 ·4H 2O, 0.2g boron powder were mixed and ground evenly, the two mixed powders were further mixed and ground together, and lanthanum nitrate was added and continued to be ground evenly, wherein the molar ratio of La to Mo was 0.1:0.9. The mixed solid powder was transferred to a porcelain boat, heated to 500℃ at 2℃ / min in an Ar atmosphere, maintained for 30min, and then heated to 800℃ at 5℃ / min, maintained for 4h. After the product was cooled, the obtained material was placed in a water bath at 90℃ for 1h to remove the residual molten salt and B x O y impurities, and then dried in a vacuum oven, recorded as 10% La-MoB x .
[0030] Comparative Example 1: First, (NH 4 ) 6 Mo 7 O 24 ·4H 2 O, boron powder, NaCl and KCl are precursor, boron source and molten salt respectively. 1.5g NaCl and 1.5g KCl are mixed and ground evenly. 0.1g (NH 4 ) 6 Mo 7 O 24 ·4H 2 O and 0.2g boron powder were mixed and ground evenly, and the two mixed powders were further mixed and ground together. The mixed solid powder was transferred to a porcelain boat and heated to 500°C at 2°C / min in an Ar atmosphere for 30 minutes, and then heated to 800°C at 5°C / min for 4 hours. After the product was cooled, the obtained material was placed in a water bath at 90°C for 1 hour to remove the residual molten salt and B x O y The impurities are then dried in a vacuum oven, and the resulting black powder is recorded as MoB x .
[0031] Performance Testing 1. Physical characterization The morphology and microstructure of the catalyst were characterized by field emission scanning electron microscopy (FE-SEM), field emission transmission electron microscopy (FE-TEM) and high resolution electron microscopy (HRTEM). Figure 1 As shown in a-1b, the FE-SEM images of all samples show uniform small-sized nanoparticle aggregates, indicating that La doping has little effect on the particle size and morphology of MoBx. Figure 1 c-1d show the TEM images of MoBx and La-MoBx, respectively. Figure 1c shows a high-resolution transmission electron microscopy (HRTEM) image of MoBx. A pair of fringes with a lattice spacing of 0.259 nm can be seen, which point to the (100) and (001) planes of MoBx. The lattice spacing of the (100) plane of La-MoBx is 0.322 ( Figure 1 e), which is much larger than the lattice spacing of MoBx, indicating that the addition of La increases the interplanar spacing. The STEM-HAADF image of La-MoBx is shown in Figure 1 As shown in f-1i, the elemental mapping image further proves that the Mo, La, B and O elements are uniformly distributed in the catalyst. It can be seen that the improvement of the electrocatalytic activity of the rare earth doped sample can be attributed to the intrinsic activity rather than the morphology and particle size.
[0032] The crystal structure of the samples was analyzed by X-ray diffractometer (Cu Kα-ray) with a scanning speed of 6° / min and a scanning angle of 10°-80°. Figure 2 a shows the 5% La-MoB prepared in Example 1 of the present invention and Comparative Example 1 x Catalyst and MoB x XRD spectrum of MoB x The match was good, indicating that a well-defined MoB was successfully synthesized. x , and the crystal structure will not change due to La doping. Figure 2 As shown in b, the full spectrum (SI) shows that Mo, B, and O elements are present in all samples, and in La-MoB x An obvious La peak appeared in the catalyst. Figure 2 d shows the high-resolution spectrum of La 3d, further confirming that La has been successfully incorporated into MoB x In addition, the high-resolution spectra of Mo 3d and B2p were fitted to study the effect of La doping on MoB x The influence of electronic structure. Figure 2 c shows MoB x The high-resolution spectra of Mo 3d of La-MoBx show three pairs of characteristic peaks at 228.28 and 231.48 eV, among which the main peak is attributed to the partially positively charged Mo δ+ 3d 5 / 2 and Mo δ+ 3d 3 / 2, the other two low-intensity peaks at 233.18 and 235.55 eV are attributed to Mo 6 + 3d 5 / 2 and Mo 6 + 3d 3 / 2, which is due to the surface oxidation of molybdenum. x In La-MoBx, Mo δ+ 、Mo 4+ and Mo 6+The three pairs of peaks are similar to those of MoB x Compared with La doped Mo δ+ The ratio of La to Mo increases significantly, which is due to the electron transfer from La to Mo caused by the electronegativity difference between La (1.1) and Mo (2.16). It can be clearly observed that the Mo 3d peak after La doping moves to a lower binding energy, indicating an increase in the electron density around Mo atoms. The increase in the electron density of Mo species can regulate the electronic state of the catalyst and promote the adsorption of hydrogen.
[0033] 2. Electrochemical characterization All electrochemical measurements were performed at room temperature using a CHI660E electrochemical workstation in a three-electrode electrochemical system. A glassy carbon electrode (GCE, diameter = 5 mm) loaded with the prepared catalyst was used as the working electrode, and a graphite rod was used as the counter electrode. 2 SO 4 In the electrolyte (pH = 0), an Ag / AgCl electrode was used as the reference electrode. All potentials in the entire experiment were switched to the reversible hydrogen electrode (RHE).
[0034] The working electrode was prepared as follows: first, 2 mg of catalyst powder and 10 μL of Nafion were added to 490 μL of isopropanol by ultrasonic dispersion to obtain catalyst ink; then, 20 μL of the ink was loaded onto the GCE with a catalyst loading mass of 0.2 mg cm -2 .
[0035] Electrocatalytic HER activity: The electrocatalytic HER activity was carried out in air. The three-electrode and electrolyte solution system used were the same as those for the electrocatalytic HER activity test. The scan rate of the test was also 5 mV s -1 The measured voltage is converted to the voltage relative to the reversible hydrogen electrode (RHE) according to the Nernst equation: , The electrochemical active surface area (EASA) is tested by the double layer method, and the size of the double layer capacitance (Cdl) is measured by cyclic voltammetry to compare the EASA size of the catalyst. It is calculated by the following two formulas: , Δj is the difference between the anodic and cathodic current densities at a given voltage; ν is the scan rate of the cyclic voltammetry test; Cs is the specific capacitance of the corresponding surface smooth sample under the same conditions (a fixed value). The voltage range of the cyclic voltammetry test is 0.1 ~ 0.2 V (vs. RHE). The three-electrode and electrolyte solution system used is the same as the electrocatalytic HER activity test, and the scan rate is from 20 mV s -1 -120 mV s -1 .
[0036] Electrochemical impedance spectroscopy (EIS) was performed using a standard three-electrode system with a catalyst-loaded glassy carbon electrode as the working electrode, Al / AlCl as the reference electrode, and a carbon rod as the counter electrode. -1 H 2 SO 4 Tested in solution, test frequency range is 10 -2 -10 5 Hz.
[0037] Electrocatalytic water splitting test: The electrocatalytic water splitting test was carried out in an H-type electrolytic cell using a two-electrode system. The catalyst-loaded working electrode was used as both the working electrode and the counter electrode. -1 H 2 SO 4 Tested in solution.
[0038] Stability test: A two-electrode system was used, with the catalyst-loaded nickel foam as the working electrode and the counter electrode. A constant voltage was applied between the two electrodes to perform a current-time (it) curve test on the catalyst.
[0039] First, MoB was detected in an acidic electrolyte. x and La-MoB x The electrocatalytic activity for HER, such as Figure 3 As shown in a, at 5 mVs -1 IR compensation LSV curve of the catalyst at a scan rate of 5%La-MoB x The catalyst has the best catalytic performance. Figure 3 As shown in b, pure MoB x 、3%La-MoB x 、5%La-MoB x 、7%La-MoB x 、10%La-MoB x The overpotential (10 mA cm −2 ) are 301mA, 206mA, 182mA, 193mA, and 215mA respectively. The intrinsic properties and mechanisms were studied using the Tafel slope method. Figure 3c, La-MoB x The Tafel slope is 48.55 mV dec -1 , less than MoB x The Tafel slope (69.98 mV dec -1 ), indicating that La doping improves the reaction kinetics. Since La doping changes the MoB x The electron density distribution of La-MoB x At 10 mA cm -2 The overpotential under current density is less than that of MoB x , which is beneficial to efficiently capture protons and improve the catalytic activity of HER.
[0040] In order to further explore the rare earth doped MoB x To investigate the mechanism of improving HER performance, electrochemical active surface area (ECSA) and electrochemical impedance spectroscopy (EIS) were tested for all samples. ECSA can be evaluated by measuring the electric double layer capacitance (CDL) in the non-Faraday range, which can reflect the effective active surface area of the catalyst. The cyclic voltammetry (CV) curves of the catalysts were tested at different scan rates, ranging from 20 to 120 mV S -1 .like Figure 3 f, MoB x and 5% La-MoB x The CDL values are 1.12 and 6.52 mF cm -2 This indicates that with the doping of La, more active centers are exposed, which effectively increases the electrochemical active surface area. As a result, the activity of the catalyst is improved. -2 , 50 mA cm -2 ) was measured under the conditions of La-MoB x The stability of Figure 3 g, both showed good stability.
[0041] On this basis, La-MoB was selected x and commercial RuO 2 As the anode and cathode of the dual-electrode system, its overall water splitting performance was further investigated. The polarization curves are shown in Figure 4 b. Obviously, La-MoB x ||RuO 2 It exhibits excellent activity at a cell voltage of 1.6 V, with a charge transfer rate of 10 mA / cm 2 Decomposes water. La-MoB x ||RuO 2 It exhibits outstanding electrocatalytic behavior, further demonstrating its excellent performance in promoting water decomposition in acidic media.
[0042] At the same time, La-MoB was studied x ||RuO 2 The overall long-term stability of Figure 4 b. After 12 h of continuous electrocatalysis, La-MoB x ||RuO 2 Still maintains excellent activity.
[0043] The present invention prepares rare earth metal La-doped MoBx nanoparticles by a simple solid-phase method combined with heat treatment. Due to the increase in the electrochemical active area and exposed active centers of the La-MoBx catalyst, the charge transfer resistance is reduced, and the charge density is redistributed, it exhibits efficient and durable hydrogen evolution catalytic performance in acidic electrolytes. The experimental results confirm that La doping can cause charge transfer, greatly modulate the electronic structure of MoBx, reduce the adsorption free energy of hydrogen, and thus improve the HER catalytic performance of MoBx. This study provides a general strategy for the synthesis of highly active catalysts by rare earth metal doping, which can be extended to the design and application of other materials.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the principle and scope of the technical solution of the present invention.
Claims
1. A rare earth doped molybdenum boride composite material, characterized in that: The rare earth element is La, and the molar ratio of the rare earth element to molybdenum is 0.03-0.1:0.97-0.
9.
2. The method for preparing the rare earth-doped molybdenum boride composite material according to claim 1, characterized in that: The following steps are involved: The molybdate precursor, boron source and flux are mixed evenly, lanthanum salt is added and ground to make the mixture evenly mixed, and the mixture is heated to the first temperature under an inert atmosphere and maintained for 20-40 min; the mixture is then heated to the second temperature and maintained for 3-5 h; after the product is cooled, it is placed in a water bath at 80-100° C. for 1-1.5 h to remove the flux and boron oxide impurities, and dried to obtain the product; The first temperature is 400-600°C; the second temperature is 700-900°C.
3. The preparation method according to claim 2, characterized in that: The molybdate precursor is any one or more of ammonium molybdate tetrahydrate, molybdic acid, lead molybdate, lithium molybdate, potassium molybdate or ammonium heptamolybdate.
4. The preparation method according to claim 2, characterized in that: The boron source is any one or more of boron powder, boric acid, sodium borohydride, boron nitride or boric anhydride.
5. The preparation method according to claim 2, characterized in that: The flux is any one or more of sodium chloride, potassium chloride, lithium chloride, calcium chloride, sodium fluoride or sodium carbonate.
6. The preparation method according to claim 2, characterized in that: The lanthanum salt is any one or more of lanthanum nitrate, lanthanum oxide, lanthanum chloride, lanthanum acetate or lanthanum citrate.
7. The preparation method according to claim 2, characterized in that: The first temperature is 400°C.
8. The preparation method according to claim 2, characterized in that: The second temperature is 800°C.
9. Use of the rare earth-doped molybdenum boride composite material according to claim 1 as a catalyst in electrocatalytic water decomposition.